Isolation and identification of Fusarium oxysporum f. sp. cubense in Fujian Province, China - Kai-li WU; Wei-zhong CHEN; Shuai YANG; Ya WEN; Yu-ru ZHENG; Wilfred Mabeche Anjago; Ying-zi YUN; Zong-hua WANG (Journal of Integrative Agriculture, 2019)
Fusarium wilt, caused by Fusarium oxyporum f. sp. cubense (Foc), is the most serious disease affecting banana production. To clarify the distribution of the Foc races in Fujian Province of China, 79 soil samples were collected from four regions of Zhangzhou City, the primary banana production area in Fujian. We isolated and identified 12 Foc strains based on internal transcribed spacer (ITS) sequence analysis, PCR amplification by using Foc-specific primers and pathogenicity assays. Our analysis indicated that 11 isolates belong to Foc race 1, and 1 isolate belongs to the Foc tropical species race 4 (TR4). Although TR4 has previously been reported to occur in primary banana-producing provinces, such as Hainan, Guangxi, and Guangdong of China, this is the first report of TR4 isolated from the soil in Fujian Province. Monitoring the presence of Foc, in particular, the TR4 strains in the soil, is the basic strategy to prevent and control Fusarium wilt.